2019
DOI: 10.1007/s42452-019-1008-0
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly synthesis and evaluation of biological activity of silver nanoparticles from leaf extract of Indigofera barberi Gamble: an endemic plant of Seshachalam Biosphere Reserve

Abstract: The present study reports the simple, rapid and ecofriendly synthesis of silver nanoparticles (AgNPs) using aqueous leaf extract of Indigofera barberi. The aqueous leaf extract of I. barberi reduces the silver ions (Ag+) into AgNPs (silver nanoparticles synthesized from I. barberi leaf extract). Fourier transform infrared spectroscopy analysis showed the broad peaks at 1054, 1371, 1589, 2355, 2933, and 3257 cm −1 which indicated the participation of polyhydroxy compounds and proteins respectively in the biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Several studies have been reported on plantassisted reduction of metal nanoparticles. The synthesis of silver nanoparticles using a wide range of plant extracts like Aloe vera [32], Myrmecodia pendans [33], Desmodium gangeticum [34], Indigofera barberi [35], Euphorbia helioscopia [36], Artimisia vulgaris [37], Taraxacum officinale [38], Convolvulus arvensis [39] is reported. The main phytochemicals responsible for biosynthesis of silver nanoparticles are alkaloids, terpenoids, phenolic compounds, enzymes, coenzymes, protein and sugars [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been reported on plantassisted reduction of metal nanoparticles. The synthesis of silver nanoparticles using a wide range of plant extracts like Aloe vera [32], Myrmecodia pendans [33], Desmodium gangeticum [34], Indigofera barberi [35], Euphorbia helioscopia [36], Artimisia vulgaris [37], Taraxacum officinale [38], Convolvulus arvensis [39] is reported. The main phytochemicals responsible for biosynthesis of silver nanoparticles are alkaloids, terpenoids, phenolic compounds, enzymes, coenzymes, protein and sugars [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the biosynthesis of metal nanoparticles (MNPs) have been proposed as a cost-effective and eco-friendly substitute to chemical methods. Many studies have been demonstrated the biosynthesis of AgNPs mediated by the microorganism or by phytochemicals or enzymatic synthesis [11,18,19,[29][30][31][32][33]. Among the biological methods, photosynthesis which involves reduction by phytochemicals derived from plants seems to be the superior choice.…”
Section: Introductionmentioning
confidence: 99%